The Internet and economic growth in least developed countries: A case of managing expectations? - Charles Kenny (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
A discussion of the theory of technology and economic growth suggests potentially negative implications for the impact of the Internet on developing countries. Technology in general is undoubtedly central to the growth process, but economists define technology in very broad terms. The impact of any particular, invented, technology is likely to be small. This theoretical perspective is supported by the empirical evidence regarding the limited impact of past `information revolutions' on least developed countries (LDCs) and the present impact of the Internet on advanced economies. Furthermore, LDCs appear ill-prepared to benefit from those opportunities that the Internet does present—they lack the physical and human capital, along with the institutions required to exploit the e-economy. Finally, even more optimistic forecasts of the Internet's global economic impact are small in scale compared to the challenge of development. This has some significant implications for development policy. – Internet ; economic growth ; developing countries
Keywords: L86; O30; O10; 330; Technologie; Internet; Wirtschaftswachstum; Vierte Welt